Comparison of synergic effects of Prilocaine and Lidocaine local anesthesia in teeth with irreversible pulpitis: A randomized clinical trial - Jalil Modaresi; Hamid Reza Hemati; Mehri Esfandyar; Mohammad Hosein Yousefi (Tehran University of Medical Sciences, 2020)
Background and Aims: Various methods to induce anesthesia have been investigated in situations where the primary inferior alveolar nerve block (IANB) injections fail. The aim of this study was to compare the effect of synergic effects of anesthetic injection of prilocaine supplemental with that of lidocaine anesthesia in teeth with irreversible pulpitis. Materials and Methods: This study was a parallel-controlled clinical trial on 58 patients with one mandibular molar tooth having irreversible pulpitis. The first anesthesia was injected with an inferior alveolar block with 2% lidocaine anesthesia. Patients who failed pulpal anesthesia were randomly divided into two groups; case and control groups. In the case group, IANB was injected with 3% prilocaine, and in the control group with 2% lidocaine anesthesia. Anesthesia after the second injection was evaluated by three methods of numerical evaluation of the patient's response to Electric Pulp Tester (EPT), the severity of the patient's response to the cold test, and the extent of pain during the onset of access cavity latency on the Visual Analog Scale (VAS). Statistical analysis was performed using T-test and Mann-Whitney tests. Results: There was no significant difference between the two groups in terms of depth of anesthesia (P>0.05). Conclusion: The results of this study showed that there was no difference between 2% lidocaine and 3% prilocaine in the depth of supplemental IANB anesthesia after failure of first IANB in mandibular molar teeth with irreversible pulpitis.